Activation of Relaxin Family Receptor 1 from different mammalian species by relaxin peptide and small molecule agonist ML290 - Huang, Zaohua; Myhr, Courtney; Bathgate, Ross A.; Ho, Brian; Bueno, Amaya; Hu, Xin; Xiao, Jingbo; Southall, Noel; Barnaeva, Elena; Agoulnik, Irina U.; Marugan, Juan; Ferrer, Marc; et al. (Frontiers in Endocrinology, 2015)
Relaxin peptide (RLN), which signals through the relaxin family peptide 1 (RXFP1) GPCR receptor, has shown therapeutic effects in an acute heart failure clinical trial. We have identified a small molecule agonist of human RXFP1, ML290; however, it does not activate the mouse receptor. To find a suitable animal model for ML290 testing and to gain mechanistic insights into the interaction of various ligands with RXFP1, we have cloned rhesus macaque, pig, rabbit, and guinea pig RXFP1s and analyzed their activation by RLN and ML290. HEK293T cells expressing macaque or pig RXFP1 responded to relaxin and ML290 treatment as measured by an increase of cAMP production. Guinea pig RXFP1 responded to relaxin but had very low response to ML290 treatment only at highest concentrations used. The rabbit RXFP1 amino acid sequence was the most divergent, with a number of unique substitutions within the ectodomain and the 7-transmembrane domain (7TM). Two splice variants of rabbit RXFP1 derived through alternative splicing of the forth exon were identified. In contrast to the other species, rabbit RXFP1s were activated by ML290, but not with human, pig, mouse, or rabbit relaxins. Using FLAG-tagged constructs, we have shown that both rabbit RXFP1 variants are expressed on the cell surface. No binding of human Eu-labeled relaxin to rabbit RXFP1 was detected, suggesting that in this species RXFP1 might be non-functional. We used chimeric rabbit-human and guinea pig-human constructs to identify regions important for RLN or ML290 receptor activation. Chimeras with the human ectodomain and rabbit 7TM domain were activated by RLN, whereas substitution of part of the guinea pig 7TM domain with the human sequence only partially restored ML290 activation, confirming the allosteric mode of action for the two ligands. Our data demonstrate that macaque and pig models can be used for ML290 testing.